Maturation induction of human peripheral blood mononuclear cell-derived dendritic cells - LI, DONG-YIN (D.A. Spandidos, 2012)
The aim of the present study was to explore an optimal method for maturation induction of dendritic cells (DCs). Human monocyte-derived DCs were induced in the presence of GM-CSF and IL-4. On Day 6, the maturation of DCs was induced with CD40L, LPS, TNF-α and cocktail of cytokines (TNF-α, IL-6, IL-1β and PGE2), respectively, for 24 h. Then, DCs were harvested and subjected to flow cytometry (FCM) for the detection of CD80, CD83, CD86 and HLA-DR. FITC-dextran endocytic activity was measured by FCM, IL-12 production by ELISA and T lymphocyte proliferation following DC stimulation by MTT assay. CD40L, LPS, TNF-α and a cocktail of cytokines induced DC maturation. Induction with the cocktail of cytokines was the most efficient, and the expression rate of CD83 was 66.91% (P<0.05). The FITC-dextran endocytic activity of mature DCs was significantly reduced, and IL-12 production was dramatically increased in mature DCs, particularly in those following induction using the cocktail of cytokines. The mature DCs had potent ability to stimulate the proliferation of lymphocytes. The cocktail of cytokines is a favorable strategy for the induction of DC maturation.